Is the Substorm Current Wedge an Ensemble of Wedgelets?: Revisit to Midlatitude Positive Bays. Issue 9 (13th September 2020) - Ohtani, Shinichi; Gjerloev, Jesper W.
Abstract: The goal of the present study is to observationally test the idea that the substorm current wedge (SCW) is an ensemble of wedgelets, mesoscale current systems that correspond to plasma sheet flow channels. According to this hypothesis, the SML index, SuperMAG equivalent to the AL index, represents a single particular wedgelet at a given time, whereas midlatitude positive bays are a sum of the remote effects of all wedgelets but with more weighting on ones closer in longitude. However, both event‐based and statistical studies of isolated substorms show that (1) midlatitude N (northward) and E (eastward) ground magnetic variations are highly correlated with SML even far from midnight; (2) the correlation between midlatitude magnetic variations and SML are organized by the magnetic local time (MLT) of the peak westward electrojet intensity (as identified by SML ), and their longitudinal structures are consistent with the conventional SCW model; and (3) eastward and westward midlatitude E variations observed at dusk and dawn, respectively, are well correlated. If the SCW is an ensemble of wedgelets, these results would imply that wedgelets with similar intensities are formed side by side throughout the SCW and evolve in parallel with each other, which is highly questionable from both physical and morphological points of view. Instead, it is suggested that the SCW is basically a globally coherent system. Although the SCW may evolve from a wedgelet formed at the onset of substorms, wedgelets are probably not a primary constituent of the SCW for most of the subsequent expansion phase. Key Points: During substorms mid‐latitude magnetic variations are highly correlated with the peak auroral electrojet intensity throughout the night side Longitudinal structures of midlatitude magnetic variations are organized by the peak location of the westward auroral electrojet intensity As a first approximation, the substorm current wedge is a globally coherent system rather than an ensemble of wedgelets